Seasonal Variability of Residence Time and Ocean Exchange in a Semi-enclosed Gulf in Northwestern Australia - Camille M. Grimaldi; Michael V. W. Cuttler; Johan Reyns; Jessica A. Benthuysen; Carolina Castro-Sanguino; Luke Thomas; James P. Gilmour; Ryan J. Lowe (Estuaries and Coasts, 2026)
Coastal water exchange with the open ocean plays a key role in regulating the transport and distribution of nutrients, heat, pollutants, suspended sediments and organisms in semi-enclosed systems. In this study, we quantify coastal water exchange for Exmouth Gulf (Australian North West Shelf), a globally significant water body adjacent to the Ningaloo Coast World Heritage Area. We use a high-resolution (200 m) hydrodynamic model, along with particle tracking, to quantify the spatiotemporal variation in circulation, water residence times, and export from the Gulf to the adjacent ocean. Water residence times in Exmouth Gulf are primarily influenced by tidal and wind forcing, with wind waves providing an additional, though secondary, contribution. The shortest Gulf residence times occurred in spring (∼52 days) and the longest in winter (∼276 days). Spatially (and across seasons), residence times within specific subregions were shortest near the western entrance (< 1 day), and longest in the southern Gulf (> 49 days). Export to the ocean was strongest during winter (albeit relatively small, accounting for only 5% of all particles), whereas during the rest of the year particles predominantly remained along the wide, shallow continental shelf to the north-east of the Gulf. Connections between the Gulf and the Ningaloo Coast World Heritage Area varied seasonally in strength, reflecting changes in the regional circulation drivers. Overall, the seasonality of regional wind patterns (via surface currents and wind waves) shaped the residence time and export of material and organisms to surrounding areas. We show that wind waves reduce residence times by up to 15% in parts of the Gulf and thus are an important component of system modelling. A thorough understanding of such dynamics is critical to make informed decisions about the conservation and management of the area.